Identifikasi Forensik melalui Analisis Perubahan Warna dan Berat Gigi Tiruan Porselen Berbasis Nilon Termoplastik akibat Paparan Suhu Tinggi - Astrid Pramadika Putri (Fakultas Kedokteran Gigi, 2025)
Fire disasters often cause damage to the environment and human remains. High temperatures can make visual identification of victims difficult. Teeth are among the few body parts that can withstand extreme heat, making them valuable for forensic identification. One potential aid in identification is the presence of dentures. Thermoplastic nylon-based dentures with porcelain artificial teeth are commonly used due to their flexibility and esthetics. This study aimed to determine the physical changes of such dentures after exposure to high temperatures in the form of changes in weight and color. Methods: This study was an experimental laboratory design using a pretest-posttest control group. A total of 16 samples of thermoplastic nylon-based dentures with porcelain artificial teeth were divided into four groups based on heating temperature: 288°C, 319°C, 412°C, and 800°C. Weight and color were measured before and after heating. Weight was measured using a digital scale. Color changes were measured using a color reader with the CIELab system. Results: All samples experienced a decrease in weight after heating. The highest reduction occurred at 800°C. Color changes were observed in both the porcelain teeth and the thermoplastic base. The most significant color change was found at 412°C. Statistical analysis showed significant differences in weight and color change depending on the temperature level (p<0.05). Conclusion: Thermoplastic nylon-based dentures with porcelain artificial teeth undergo significant physical changes after exposure to high temperatures. These changes can be used to support forensic identification in fire victims.
Entry oleh Arif 2026 April 01
Keywords: Fire; Forensic Identification; Thermoplastic Nylon; Porcelain Artificial Teeth; Color Change; Weight Loss